THE PALEOCHRONOLOGICAL STAGES OF ANIMAL EVOLUTIONMAIN - AJAY KUMAR (International Journal of Multidisciplinary Research and Studies, 2020)
Paleochronology is the study of the timing and duration of events in the history of the Earth, and it plays a crucial role in understanding the evolution of animals. This article outlines the major paleochronological stages of animal evolution, including the Ediacaran period, Cambrian explosion, Ordovician period, Silurian period, Devonian period, Carboniferous period, Permian period, Mesozoic era, Cenozoic era, Paleogene period, Neogene period, and Quaternary period. By examining these stages, we can better understand the sequence of appearance and disappearance of various animal groups and the timing of major evolutionary transitions. Moreover, understanding the paleochronological stages of animal evolution is crucial for predicting the future of life on Earth. The ongoing biodiversity crisis highlights the importance of preserving and protecting the diversity of species that have evolved over millions of years. By understanding the historical context of animal evolution, we can better understand how species have responded to past environmental changes and use this information to inform conservation efforts and mitigate the impact of current and future environmental changes.